Osseointegrated reconstruction and rehabilitation of transtibial amputees: the Osseointegration Group of Australia surgical technique and protocol for a prospective cohort study. Issue 10 (20th October 2020) - Haque, Russel; Al-Jawazneh, Shakib; Hoellwarth, Jason; Akhtar, Muhammad Adeel; Doshi, Karan; Tan, Yao Chang; Lu, William Yenn-Ru; Roberts, Claudia; Al Muderis, Munjed
Abstract : Introduction: Lower extremity amputation uniformly impairs a person's vocational, social and recreational capacity. Rehabilitation in traditional socket prostheses (TSP) is associated with a spectrum of complications involving the socket-residuum interface which lead to reduced prosthetic use and quality of life. Osseointegration has recently emerged as a novel concept to overcome these complications by eliminating this interface and anchoring the prosthesis directly to bone. Though the complications of TSPs affect both transfemoral and transtibial amputees, Osseointegration has been predominantly performed in transfemoral ones assuming a greater benefit/risk ratio. However, as the safety of the procedure has been established, we intend to extend the concept to transtibial amputees and document the outcomes. Methods and analysis: This is protocol for a prospective cohort study, with patient enrolment started in 2014 and expected to be completed by 2022. The inclusion criteria are age over 18 years, unilateral, bilateral and mixed transtibial amputation and experiencing socket-related problems. All patients receive osseointegrated implants, the type of which depend on the length of the residuum and quality of bone, which are press-fitted into the residual bone. Objective functional outcomes comprising 6-Minute Walk Test, Timed Up-and-Go test and K-level, subjective patient-reported-quality-of-life outcomes (Short Form Health Survey 36, daily prosthetic wear hours, prosthetic wear satisfaction) and adverse events are recorded preoperatively and at postoperative follow-up intervals of 3, 6, 12 months and yearly, and compared with the preoperative values using appropriate statistical tests. Multivariable multilevel logistic regression will be performed with a focus to identify factors associated with outcomes and adverse events, specifically infection, periprosthetic fracture, implant fracture and aseptic loosening. Ethics and dissemination: The Ethics approval for the study has been received from the University of Notre Dame, Sydney, Australia (014153S). The outcomes of this study will be disseminated by publications in peer-reviewed academic journals and scientific presentations at relevant orthopaedic conferences.